Dominant Factors Affecting HIV AIDS Prevention In The Village “X” Bongas District Of Indramayu In 2023 - Wardani, Siti Pangarsi Dyah Kusuma; Astuti, Nur Mega; Nuraeni, Tating (Universitas Wiralodra, 2024)
Data from the health service of Indramayu district in 2021 showed that the number of cases of HIV AIDS was 4,849 per incidence in Indramayu district, with the highest cases in Bongas district being 392. The research was conducted in the village